Ontogenetic characterization of Phytoseius huaxiensis (Acari: Phytoseiidae) - Feng, Xiao; Liu, Yu; Diao, Chun-Xia; Fan, Qing-Hai; Ma, Min (Zootaxa, 2025)
Morphological ontogeny provides critical insight into character polarity, stage-specific diagnostic traits, and evolutionary relationships in Phytoseiidae. To advance understanding of these aspects, we reared Phytoseius huaxiensis Xin, Liang & Ke under controlled laboratory conditions and documented its complete developmental stages—larva, protonymph, deutonymph, and adult. Each stage is described and illustrated, with emphasis on diagnostic features and ontogenetic changes in dorsal shield structure, idiosomal and leg setation, and gnathosomal morphology. Comparative analysis with other phytoseiid taxa reveals both conserved and divergent traits, refining genus-level diagnoses and contributing to phylogenetic interpretation across the family.